A new peptaibol, RK-026A, from the soil fungus Trichoderma sp. RK10-F026 by culture condition-dependent screening. Issue 1 (7th January 2021) - Rawa, Mira Syahfriena Amir; Nogawa, Toshihiko; Okano, Akiko; Futamura, Yushi; Nakamura, Takemichi; Wahab, Habibah A; Osada, Hiroyuki
Abstract: A new peptaibol, RK-026A (1 ) was isolated from a fungus, Trichoderma sp. RK10-F026, along with atroviridin B (2 ), alamethicin II (3 ), and polysporin B (4 ) as a cytotoxic compound, which was selected by principal component analysis of the MS data from 5 different culture conditions. The structure of 1 was determined as a new atroviridin B derivative containing Glu at the 18th residue instead of Gln by NMR and HR-MS analyses including the investigation of detailed MS/MS fragmentations. 1 showed cytotoxicity toward K562 leukemia cells at an IC50 value of 4.1 µm . Graphical Abstract: